Understanding ASF dynamic in South Africa: from spatio-temporal analysis at national level to fine special network analysis - (:unkn) unknown (My University, 2019)
Since the first probable ASF outbreak occurred in the Koedoesrand Ward in 1926, South Africa has experienced many other outbreaks that can be divided temporally into 2 time periods; the period before the development of the OIE disease database and the period after. More than 143 outbreaks of swine fever were reported during the first period but not all were clearly defined as classical swine fever (CSF) or ASF. Since the development of the OIE disease database (1993), 72 outbreaks directly involving 2968 cases mainly in smallholder pig farms were reported. Outbreaks occurred mainly in Northern provinces part of the control zone defined in 1935. Since 2012, outbreaks tended to be more likely to occur in the free zone. In order to better understand the context in which African Swine Fever (ASF) outbreaks occurred in South Africa we described temporal, spatial distribution of reported ASF outbreaks in South Africa and examined spatio-temporal structure of ASF outbreak clusters in South Africa. Multi-Distance Spatial Cluster Analysis was used to assess the spatial clustering using ArcGIS 10.6, spatiotemporal clusters analyses were carried out using the R package splancs and scanning was utilised to identify spatiotemporal clusters of the disease using SaTScan. A specific focus was the particular zone of Northern Kwa-Zulu Natal (NKZN) bordering Mozambique and Eswatini (formerly Swaziland) defined by the zoning policy as a control zone. A spatialized social network analysis was used in order to assess the relevance of this zoning as no ASF outbreak was ever reported. Pig movement patterns were analysed using Social Network analysis (SNA) in R software. This network was georeferenced and a map of pig movements was produced. In the second phase farms, origins and destinations were grouped by villages and the villages represented the nodes of the network while directed arcs referred again to pig movement. Sociograms or link graphs were drawn using the igraph pa
Keywords: African Research